Immune, metabolic, anatomical, and functional features of people after successful tuberculosis treatment: an exploratory analysis - Webber, Tariq; Macdonald, Candice; Tameris, Michele; Tredoux, Nicolette; Bierman, Anandi; Gutschmidt, Andrea; Tönsing, Susanne; Hiemstra, Andriëtte; Noor, Firdows; Snyders, Candice; Richardson, Tracy; Fransman, Bernadine; et al. (Scientific reports, 2025)
We explored the underlying mechanisms that may drive post-tuberculosis (TB) lung disease, a multifactorial, heterogenous, and prevalent disease. Extensive clinical phenotyping through fluorine-18 Fluorodeoxyglucose (FDG) positron emission tomography (PET)-computed tomography (CT) scans, pulmonary function testing, and symptom and quality of life questionnaires, was performed on a cohort of 48 adults who completed TB treatment within 6 months prior. Immunological characteristics of paired blood- and bronchoalveolar lavage fluid (BALF)-derived immune cells were assessed by multiplex bead-based immunoassay, ELISA and flow cytometry. There was agreement between measures of inflammation on PET, the severity of anatomical abnormalities on CT, and pulmonary function testing. However, of these, only PET was associated with exercise tolerance and symptom scores. Measures of radiologic extent (total glycolytic activity and SUVmax on PET, and segments involved on CT) also correlated with proteins detected in blood that implicate type 1 (IFN-γ, TNFα, IL-12) and type 2 (IL-4, IL-33) responses, ongoing remodelling of lung tissue (MMPs), airways and vasculature (VEGF), as well as subsets of activated CD8 + and CD4 + T-cells. The radiologic extent of structural post-TB lung involvement is associated with a range of impaired lung function measures and immunological dysregulation. Our findings suggest that obstructive and restrictive lung pathology due to pulmonary TB do not occur in opposition but rather point towards a mixed pathology in most TB survivors.